The Relationship Between Stress And Acne Severity In Students Of Nursing Study Program Level III At Santa Elisabeth College Of Health Sciences Medan In 2024 - Lilis Novitarum; Jagentar P. Pane; Aprillia Deliana Simanjuntak (Jurnal EduHealth, 2025)
Stress is a physiological and psychological condition that occurs when a person is faced with pressure or situations that are considered to threaten the balance of his life. Stress can cause various pathophysiological conditions, one of which is acne. The research used quantitative researchers with a cross-sectional approach. The sampling technique in this study used total sampling with a sample size of 97 respondents. The results of the study showed that respondents had more moderate stress levels of 50 respondents (51.5%) and moderate acne severity of 49 respondents (50.5%). The results of the Spearman rank statistical test obtained a p-value = 0.108 (p>0.005), meaning that Ho was accepted - there was no relationship between stress and acne severity in third-year nursing study program students at the Santa Elisabeth Health Sciences College, Medan in 2024. There is no relationship between stress and the severity of acne in third-year nursing students at the Santa Elisabeth Health Sciences College, Medan in 2024.